Allium sativum antimicrobial potential in fresh cheese (Research, Society and Development, 2021)
Cheese consumption has shown an important increase throughout the Brazilian territory, being the second most    imported product since 2015. Among the different types of cheese, minas frescal represents one of the most popular, due to its simple processing, low cost and high yield. However, its perishability requires refrigeration and relatively fast consumption, thus representing an important limiting factor in commercialization. Aspects such as having a high moisture content, not undergoing maturation, and containing no preservatives, provide favorable conditions for microbiological contamination. Thus, it was aimed to assess the antimicrobial potential of the aqueous suspension of garlic (SAA), in fresh cheese before and after contamination Staphylococcus aureus (ATCC 25923) 105 CFU mL-1. The minimum inhibitory concentration (MIC) was determined by microdilution, and the following treatments were evaluated in quintuplicate: SAa in freeze-dried and fresh forms (1.5; 2.5; 5; and 10%), negative control treatment (cheese absent contamination), and positive (cheese absent from SAa). After superficial inoculation in Agar Baird Parker, enriched with egg yolk and potassium tellurite, the incubation was performed at 35ºC for 48 hours. Although SAa in lyophilized and fresh form applied before contamination did not show antibacterial activity, the fresh form applied after contamination showed a MIC equivalent to 2.5%. So, based on the results obtained by the present study, it was possible to conclude that SAa above 2.5% had antimicrobial properties, thus favoring the conservation of fresh cheese.